Encapsulation of ultra small metal clusters in silica: evolution of the concept of nanoreactors and the case of Ag-Pd@SiO2 alloy catalyst - Mondal, Sourik; Samanta, Anupam; Dhar, Basab B.; Devi, R. Nandini (Catalysis Today, 2015)
The concept of encapsulation of ultra small clusters within silica evolved as a means to address the sintering of active metal nanoparticles and subsequent deactivation observed in supported noble metal catalysts. It is hypothesised that sintering, which mainly occurs due to mobility of metal species on the support surfaces, can be minimised if the growth and movement of metal nanoparticles are constrained. First, nanoparticles are isolated inside 1D channels in 2D mesoporous compounds and the idea develops to complete encapsulation of thiol protected ultra small nanoclusters in silica spheres. Sintering is better controlled in the latter due to the confined space for growth of nanoparticles. Access of reactant molecules to the active metal surfaces also is ensured by porosity created in the silica matrix forming the basis of the concept of nanoreactors. In this paper, we elaborate on the evolution of this concept from our earlier work on highly sinter resistant silica encapsulated Au, Pd and Au-Pd alloys to the present system of Ag-Pd alloy encapsulated in silica. Silver, with the lowest Tammann temperature among noble metals, is highly prone to sintering which is adequately controlled by alloying with Pd as well as encapsulation in silica. Its enhanced activity in paranitrophenol reduction in comparison with pure metals indicates the advantageous effect of alloying. (C) 2014 Elsevier B.V. All rights reserved.
7th Tokyo Conference on Advanced Catalytic Science and Technology (TOCAT), Kyoto, JAPAN, JUN 01-06, 2014
Keywords: Ag-Pd alloy; Encapsulation; Sinter resistant; Sintering; Ultra small nanoclusters